Conflicto armado, contaminación y riesgos en salud: Una evaluación de riesgo por tres fuentes de exposición ambiental asociadas al conflicto en Colombia (2021)
ntroduction: Armed conflicts affect territories rich in resources and biodiversity; As a result of the environmental damage caused by violent actions, the health of populations can be affected. Objectives: To assess the risks to human health due to environmental degradation associated with three violent actions related to the Colombian armed conflict: pipeline bombing, informal mining with mercury, and spraying of illicit crops with glyphosate. Materials and methods: A quantitative evaluation of the risks to individual health associated with activities of the armed conflict was developed, using methodologies that take into account the routes of dispersion of pollutants, concentrations in the environment, exposure of individuals and risks of carcinogenic and non-carcinogenic effects. Results: The risk assessment for the types of actions related to the armed conflict included in this study showed evidence of intolerable carcinogenic risk and unacceptable non-carcinogenic risk due to the consumption of water and fish contaminated by PAH, mercury and glyphosate. Conclusions: This study reaffirms the inextricable connections that exist between the environment, society, and health and the implications of environmental violence for the public health of these vulnerable population groups and, in general, for the well-being of all living beings affected by the armed conflict.